INTEGRATION OF SIMULATION TECHNOLOGIES WITH PHYSICAL SYSTEM OF RECONFIGURABLE MATERIAL HANDLING - Abdul Rahman, A.A.; Osman, M.S.; Ng, R.; Abdullah, S.; Rahman, M.A.A.; Mohamad, E.; Abdul Rahman, A. (Journal of Advanced Manufacturing Technology (JAMT), 2018)
The rapid-changing manufacturing environment requires a manufacturing system that is easily upgradeable to match new technologies and new functions such as Reconfigurable Manufacturing System (RMS). RMS is distinctive from the conventional manufacturing system, where the RMS can be accomplished by using reconfigurable hardware and software, such that its capability and functionality are changeable over time. The reconfigurable components of a RMS include mechanisms, material handling system, sensors control algorithms, machines and modules for the whole production system. The objective of this project is to verify the integration between a simulation with a physical system of a reconfigurable material handling, in order to allow the simulation software controls the physical system directly. The methodology of this project starts with modelling of the physical system. Then, the control logic of the physical system model is constructed in simulation software in line with the behavior of the real physical system. Next, PLC as the controller of reconfigurable material handling connects a computer through OPC server. The PLC communication tags are extracted from OPC server. These tags are used to build the communication between simulation and OPC server. As a result, the integration capabilities are verified by using data comparison over time between simulation and reconfigurable conveyor system.